Responsabilidade tributária: solidariedade e subsidiariedade - Darzé, Andréa Medrado (2009)
The objective of the present work is to study the norms of solidary and subsidiary tax responsibility under two perspectives: static and dynamic. We began our research by seeking to answer to the following questions: what are the constitutional and legal limits for the choice of the taxpayer of the tax legal? What is the calculation that establishes the relationship between the rule of tax incidence in broad sense and the rules on liability? After intense discussions, we conclude that the legislature may charge the duty to pay taxes to subject other than that held its materiality ensure that only when the financial burden of taxation is likely to pass on the display of wealth that gave him cause. We, also, noticed that the need for indirect linkage to the support of responsible tax or tribute of the subject that made the two alternatives were chosen by positive law to ensure compliance with this requirement. Finally, we explained the suitable legislative vehicle to promote the insertion of the image of the tax responsible in the system varies because of the very connection type which the responsible maintains with the assumption of tax fact, whether objective or subjective. Identified the requirements for the establishment of rules for tax liability, we present, dynamically, the possible patterns of species of tax liability under Nacional Tax Code. After that, we found that the calculation of the relations established between the rule of tax incidence in the broad sense and the responsibility rule is not dictated by the species of responsibility of the case, but by its characteristics: whether exclusive, solidary, or subsidiary. In a second moment, we set the scope and content of signs solidarity and subsidiarity on tax, stating the characteristics that bring together these two legal institutions and move them away. Also, we factored analytically the main examples of these ties under tax law. , concluding that the concomitant notification of all of the solidary and subsidiary codebtors is requirement of validity of the release action or of the infraction solemnity and fine imposition. That circumstance will only be able to be outlined in the eventuality of the knowledge of the fact of the responsibility to be subsequent to the emission of those norms, be because the own passive subject was used of artifices to hide his/her occurrence, be because the event of the responsibility was indeed practiced in a second instant. Finally, we examined the conditions for the drafting of individual and specific rule in such cases, concluding that the concomitant notification of all solidary and subsidiary co-debtors is a requirement of validity of the act of publication the tax notice and imposition of fine. That circumstance can only be avoided if the knowledge of the fact that the responsibility is subsequent the issuance of these rules, either because the taxpayer concealed his occurrence, or because the event of liability was actually practiced in a second moment